Hormonal regulation of farm animal growth - Hossner, K. L. [ (Kim L.)] (CABI Publishing, 2005)
This book describes the cellular and molecular mechanisms that are involved with the regulation of cell and tissue growth, including development and body composition. The emphasis is on circulating hormones, local growth factors and gene transcription fctors which regulate growth and differentiation of skeletal muscle, bone and adipose tissue.